The Power of Developmental Performance Appraisal - Nasser Salim Alghanabousi; Muhammad Faizal A. Ghani; Faisol Elham (Intelektual Pustaka Media Utama, 2013)
Development of employee performance is a must that any organization should take into account to be a successful in achieving its goals. However, the tools of developing that performance are varying based on the type of the organization and the nature of the work performed. Performance appraisal is one of the effective tools that help the organization to measure the accomplishment of its goals, if implemented effectively. In education, it became evident that performance appraisal of educators is an essential element of the development of any educational institution. To make the performance appraisal fruitful, the development element should be dominant in the sense that other elements of the appraisal should serve the broad aim of the appraisal process. Therefore, a well-designed and comprehensive system is needed to cover all the aspects of appraisal process that include of the goals, criteria, instruments, and continuous support.